Evaluation Of Patient Satisfaction In The Service Of The Lembang Hospital Heart Poly - Rachmi Anasthasia Seriulna; Kosasih, Kosasih; ⁠Eka Purwanda (Sean Institute, 2024)
This study aims to evaluate the level of patient satisfaction with the services at the Lembang Hospital Heart Poly. Patient satisfaction is one of the key indicators in assessing the quality of health services provided, especially in cardiac specialist services that require more attention. The method used in this study involves a questionnaire survey to patients who have received services at the Lembang Hospital Heart Poly. The aspects assessed include the speed of service, the competence of medical personnel, facilities, and the comfort of the hospital environment. The results of the study showed a high level of patient satisfaction in terms of the competence of medical personnel and facilities, but there were several complaints about the speed of service that needed improvement. This finding is expected to be an evaluation material to improve the quality of services in the future.